2000
DOI: 10.1007/bf02491024
|View full text |Cite
|
Sign up to set email alerts
|

Automated flow system on-line to LC with postcolumn derivatisation for determination of sugars in carbohydrate-rich foods

Abstract: KeyWordsColumn liquid chromatography Postcolu mn derivatisation Sugars Carbohydrate-rich foods SummaryA method for the direct determination of carbohydrates in foods using an automated-flow system coupled on-line to a high-performance liquid chromatograph is proposed. The method is based on postcolumn clerivatisation of reducing sugars with p-aminobenzoic acid hyclrazide in an alkaline medium following elution from the chromatographic column with an acetonitrile:water graclient as mobile phase. The manifold al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…In recent years, a high performance liquid chromatographic method with postcolumn fluorescence derivatization has been developed to determine sulfated carbohydrates in biological samples [13,14,15,16,17]. This method is convenient and automatic.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, a high performance liquid chromatographic method with postcolumn fluorescence derivatization has been developed to determine sulfated carbohydrates in biological samples [13,14,15,16,17]. This method is convenient and automatic.…”
Section: Introductionmentioning
confidence: 99%
“…This work showed that high‐resolution NMR spectroscopic methods could provide a rapid and efficient means of investigating microbial metabolism directly without invasive or destructive sample pretreatment. van Eijk developed a high‐throughput screening method using LC–MS (Caceres et al , 2000; van Eijk et al , 1999) to study the amino acids, in which the simultaneous application (and thus measurement) of multiple amino acid tracers was used coupled to liquid chromatography and mass spectrometry, resulting in the measurement of both the concentration and isotope enrichment of O ‐phthaldialdehyde (OPA)‐derivatized plasma amino acids in one run. Considering the easier and cheaper derivatization procedure and instrumentation, the simultaneous collection of isotopomeric distribution spectra (enabling the application of multiple labelled components) and concentration data, the method presents an attractive alternative to traditional GC–MS applications for amino acids.…”
Section: Introductionmentioning
confidence: 99%
“…Supercritical fluid extraction with different detectors 8 has also been proposed. Liquid chromatography is the alternative of choice for the individual determination of carbohydrates in milk. Amperometric biosensors, capillary electrophoresis, gas chromatography, and flow systems with UV−vis detection have also been referenced.…”
mentioning
confidence: 99%